Combining abilities and heterotic groups in Pisum sativum L. - Espósito, María Andrea (2013)
The objective of this research was to investigate the use of heterosis and estimates of the general combining ability (GCA) and specific combining ability (SCA) for yield and the yield-related traits for identifying suitable parents and forming heterotic groups for pea- breeding programs. Seventy-six F1 hybrids derived from crosses between nineteen female lines and four male testers were evaluated during two seasons. Estimates of variance due to GCA and SCA effects and their relationship revealed predominantly additive effects for all traits. Parents with higher GCA values were "ZAV20" (female parent) and "ZAV23" (male parent).The cross "ZAV5 x ZAV23" showed the highest value for seed yield. Days to flowering and number of seeds per plot were the variables with the highest values for broad and narrow-sense heritability (0.93 and 0.65, respectively), indicating that these traits are highly heritable. The highest best parent heterosis for seed yield was observed in the "ZAV17 x DDR14" hybrid. Four heterotic groups were formed and validated by estimating the intra and inter group heterosis.